(untitled) (Trabalho & Educação, 2017)
prison education in Pará state This text systematizes the results of a research carried out within the framework of the Observatório Nacional do Sistema Prisional (ONASP) about prison education in Brazil and is also articulated to a postdoctoral study. Its elaboration sought to deepen and contribute to the existing discussions on prison education. We show the difficulties that such discussions have had in the field of the implementation of an education program, capable of being linked to the functional diagram of prison systems, whose formative character is essentially disciplinary and punitive. It was carried out based on the categories of work and education as constitutive elements of the people and in it we identified the fundamentals and main references on the subject, also bringing data about the configuration of education in prison in a national setting and more specifically in the Amazon of Para. The text was developed through bibliographical research, including a review of the literature and the reports produced in this field, in order to problematize the categories of labor and prison education as possibilities for human emancipation. We affirm that the education model based on oppression and the maintenance of order does little to re-socialize those incarcerated and that the educational proposals in the prison portray the limits, the few advances and some possibilities of a process of the construction of new parameters for the quality of the education offered in the prison. ___ Este texto sistematiza os resultados de pesquisas realizadas no âmbito do Observatório Nacional do Sistema Prisional (ONASP) acerca da educação carcerária no Brasil e também está articulado a um estudo pós-doutoral. Sua elaboração buscou aprofundar e contribuir com as discussões existentes sobre a educação em prisões. Evidenciamos as dificuldades que tais discussões têm tido no campo da efetivação de um programa de educação, capaz de estar ligado ao diagrama funcional dos sistemas prisionais, cujo caráter formativo é essencialmente disciplinar e punitivo. Foi realizado tomando por base as categorias trabalho e educação como elementos constitutivos das pessoas, e nele identificamos os fundamentos e as principais referências acerca do tema, trazendo, ainda, dados sobre a configuração da educação no cárcere em cenário nacional e, mais especificamente, na Amazônia paraense. O texto foi desenvolvido por meio de pesquisa bibliográfica, incluindo a revisão da literatura e dos relatórios produzidos nesse campo, com fins de problematizar as categorias trabalho e educação carcerária como possibilidades de emancipação humana. Afirmamos que o modelo de educação que tem como fundamento a opressão e a manutenção da ordem pouco contribui com a ressocialização dos encarcerados e que as propostas educativas no cárcere retratam os limites, os poucos avanços e algumas possibilidades de um processo que se estabelece sob a égide da construção de novos parâmetros para a qualidade da educação ofertada nas unidades prisionais.